Design and Fabrication Technology of Metal Mirrors Based on Additive Manufacturing: A Review - Kai Zhang; Hemeng Qu; Haijun Guan; Jizhen Zhang; Xin Zhang; Xiaolin Xie; Lei Yan; Chao Wang (Applied Sciences, 2021)
In recent years, much progress has been made on the development of metal mirrors based on additive manufacturing (AM). The sandwich mirror is well known for its excellent mechanical properties and challenging machining. Now, AM can be used to fabricate this complex structure and reduce the processing time and cost. In addition, with the aid of some new design methods for additive manufacturing, such as lattice, topology optimization (TO), and Voronoi, the freedom of mirror structure design is enormously improved. The common materials of mirrors include ceramics (SiC), glasses (glass ceramics, fused silica), and metals (aluminum, beryllium). Among them, the AM technology of metals is the most mature and widely used. Researchers have recently extensively developed the new-generation metal mirror to improve performance and lightweight rate. This review focuses on the following topics: (1) AM technologies and powder materials for metal mirrors, (2) recent advances in optomechanical design methods for AM metal mirrors, (3) challenges faced by AM metal mirrors in fabricating, and (4) future trends in AM metal mirrors.